Standardization of Vascular Assessment of Erectile Dysfunction. (12th September 2012) - Sikka, Suresh C.; Hellstrom, Wayne J.G.; Brock, Gerald; Morales, Antonio Martin
ABSTRACT Introduction. In‐office evaluation of erectile dysfunction by color duplex Doppler ultrasound (CDDU) may benefit the decision‐making process in regard to choosing the most appropriate therapy. Unfortunately, there is no uniform standardization in performing CDDU resulting in high variability in data expression and interpretation when comparing results among various centers, especially when conducting multicenter trials. Establishing standard operating procedures (SOPs) is a major step that will help minimize such variability. Aim. This SOP describes CDDU procedure with focus on establishing uniformity and normative parameters. Main Outcome Measure. Measure intra‐arterial diameter, peak systolic velocity, end‐diastolic velocity, and resistive index for each cavernosal artery. Methods. After initial discussion with the patient about his history and International Index of Erectile Function evaluation describe procedural steps to the patient. Perform the CDDU in a relaxed state, scanning the entire penis (in B‐mode image) using a 7.5‐ to 12‐MHz linear array ultrasound probe. An intracorporal injection of a single or combination of vasoactive agents (e.g., prostaglandin E1, phentolamine, and papaverine) is then administered and CDDU performed at various time points, preferably with audiovisual sexual stimulation (AVSS). Results. Monitor penile erection response (tumescence and rigidity) near peak blood flow. Self‐stimulation or AVSS leaving the patient alone in room or redosing may be considered to decrease any anxiety and help achieve a maximum rigid erection. Conclusion. Considering the complexity and heterogeneity of CDDU evaluation, this communication will help in standardization and establish uniformity in such data interpretation. When indicated, invasive diagnostic testing involving (i) penile angiography and (ii) cavernosography/cavernosometry to establish veno‐occlusive dysfunction may be recommended to facilitate further treatment options. Sikka SC, Hellstrom WJG, Brock G, and Morales AM. Standardization of vascular assessment of erectile dysfunction. J Sex Med **;**:**–**.